Kepuasan Pelanggan sebagai Faktor Kualitas Pelayanan PT. Mada Graha Nagata dengan Multi Attribute Attitude Model - Rudy Sondang Sinaga; Kalvin Sinaga; Ahmad Prayudi; Henny Pratiwi; Fahmi Sulaiman (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
There are still customers who are dissatisfied with Izone's performance as evidenced by several customer complaints against Izone, including (a) The distance to public facilities such as toilets (b) Some consumers complain about hot karaoke air conditioners (c) The price of the starter power card package (because there is no expiration date) (d) More and varied gift items for the promo (e) The number of machines that are swiped can't play (because consumers swipe wrong) (f) Izone is only in the Irian Supermarket Dept. Store. If this is not handled quickly and seriously, it will cause big losses for iZone. The purpose of this study was to determine customer satisfaction with service quality at PT. Mada Graha Nagata This research was carried out from July 2019 to September 2019 It was carried out at the PT. Mada Graha Nagata Tembung Deli Serdang Branch. Quantitative marketing research methods can be defined as marketing research that conveys research objectives through empirical assessment involving various numerical measurements and various analytical approaches. This type of research uses a descriptive design. The conclusions that can be drawn in this research are from the value of each attribute, the Multi-attribute Attitude Model (MAM) obtained the overall attitude value is as follows: (-28) + (-14.3) + (26 ,8) + (30.2) + (68) = 82.7. The value of 82.7 is included in the Neutral range, it can be concluded that visitors rate Neutral on the service quality of PT. Mada Graha Nagata (Izone2000).